Indoor heating triggers bacterial ecological links with tap water stagnation during winter: Novel insights into bacterial abundance, community metabolic activity and interactions. (15th January 2021) - Zhang, Haihan; Xu, Lei; Huang, Tinglin; Liu, Xiang; Miao, Yutian; Liu, Kaiwen; Qian, Xuming
Abstract: The overnight stagnation of tap water in plumbing systems can lead to water quality deterioration. Meanwhile, the indoor heating can improve the indoor temperature in cold areas during winter, which may affect the quality of tap water during stagnation. However, indoor heating drives bacterial ecological links with tap water stagnation during winter are not well understood. The results indicated that the water temperature increased significantly after stagnation during indoor heating periods. Moreover, the average intact cell number and total adenosine triphosphate (ATP) concentration increased 1.53-fold and 1.35-fold after stagnation, respectively ( P  < 0.01). In addition, the increase in the ATP per cell number indicated that the combined effects of stagnation and indoor heating could enhance the bacterial activity. Biolog data showed that the bacterial community metabolic capacity was significantly higher in stagnant water than that of fresh water. Co-occurrence networks suggested that the bacterial metabolic profile changed after stagnation during the heating periods. DNA analysis indicated that the composition of the bacterial community changed dramatically after stagnation. The abundances of potential pathogens such as Mycobacterium sp. and Pseudomonas sp. also increased after stagnation. These results will give novel insights on comprehensive understanding the combined effects of indoor heating and overnight stagnation on the water bacterial community ecology of plumbing systems, and provide a scientific basis for tap water quality management after overnight stagnation during the indoor heating periods. Graphical abstract: Image 1 Highlights: Water temperature increased after overnight stagnation. Intact bacterial cell and ATP concentrations increased after stagnation. Overnight stagnation triggers water bacterial community activity. Co-interactions of bacterial community were complex in stagnant samples. Abundances of OPPPs increased in the stagnant water. Abstract : In the building ecosystems, the tap water temperature increased significantly and water quality changed after stagnation during indoor heating periods in winter.